Surface features of TIG melting coated CP-titanium - Adeleke, S.A.; Maleque, Md. Abdul (Trans Tech Publications, Switzerland, 2015)
Tungsten inert gas (TIG) melting process is increasingly find successful application in many aspects of engineering part components. In this study, TIG melting of Fe-based coating has been successfully developed by precoated iron, carbon and silicon (Fe-C-Si) powders on commercial purity titanium (CP-titanium) surface under three different glazing speeds such as 1.0 mm/s, 1.5 mm/s and 2.0 mm/s and constant energy input of 1350 J/mm in an argon gas environment. The effects of glazing speeds on the surface topography, melt geometry, microstructure and hardness were investigated. Rippling marks were found on all the track surfaces which portends that good solidification of the molten melt pool had taken place near the base metal. The melt pool layers consisted of higher population of dendrites and the population were found to decrease with increasing glazing speeds. The resolidified surface layer of the dendrites developed hardness 3 to 4 times higher than that of the base material. According to the enthalpy reactions due to formation of titanium carbide, silicon carbide and iron carbide during TIG melting of Fe-C-Si coated titanium surface are considered to be responsible for larger melt depth. These results showed that surface properties of CP-titanium can be enhanced with Fe-C-Si using TIG melting process.